ψ (3770) resonance and its production in p ¯ p →D D ¯ - Haidenbauer, J.; Krein, G. [UNESP] (American Physical Society (APS), 2015)
The production of a DD¯ meson pair in antiproton-proton (p¯p) annihilation close to the production threshold is investigated, with special emphasis on the role played by the ψ(3770) resonance. The study is performed in a meson-baryon model where the elementary charm production process is described by baryon exchange. Effects of the interactions in the initial and final states are taken into account rigorously, where the latter involves also those due to the ψ(3770). The predictions for the DD¯ production cross section are in the range of 30-250 nb, and the contribution from the ψ(3770) resonance itself amounts to roughly 20-80 nb.